A comprehensive landscape analysis of autophagy in cancer development and drug resistance - Li, Yue; Yin, Yang; Zhang, Tong; Wang, Jinhua; Guo, Zeqi; Li, Yuyun; Zhao, Ya; Qin, Ruihong; He, Qian (Frontiers in Immunology, 2024)
Background: Autophagy plays important roles in cancer progression and therapeutic resistance, and the autophagy underlying tumor pathogenesis and further mechanisms of chemoresistance emergence remains unknown.Methods: In this study, via the ssGSEA method, an autophagy 45-gene list was identified to evaluate samples' autophagy activity, verified through six GEO datasets with confirmed autophagy phenotype. Further utilizing it to distinguish tumor to autophagy score-high and score-low subtypes, and analyzed their transcriptome landscapes, including survival analysis, correlation analysis of autophagy-and resistance-related genes, biological functional enrichment, immune and hypoxiarelated and genomic heterogeneity comparison, in TCGA pan-cancer datasets. Furthermore, we performed the analysis of autophagy status in breast cancer chemoresistance combined with multiple GEO datasets, and experiments in vitro to validate the mechanisms of potential anti-cancer drugs for reversing chemoresistance, including CCK-8 cell viability assays, RT-qPCR and immunofluorescence.Results: Utilizing 45-gene list to identify autophagy score-high and score-low subtypes, and further analyzed their multi-dimensional features. We demonstrated cancer autophagy status correlated with significantly different prognosis, molecular alterations, biological processes activation, immunocyte infiltration, hypoxia status and specific mutational processes. The autophagy score-low subtypes displayed the more favorable prognosis compared with score-high, associated with their immuneactivated features, manifested as high immunocyte infiltration, including high CD8+T, Tfh, Treg, NK cells and tumor-associated macrophages M1/M2. Autophagy score-low subtype also showed high hypoxia score, and hypoxic tumors showed significantly differential prognosis in different autophagy status. Therefore, "double-edged" cell fates triggered by autophagy might closely correlated with immune microenvironment and hypoxia induction. Results demonstrated that dysregulated autophagy was be involved in many cancers and their therapeutic resistance, and the autophagy induced by the resistance-reversing drugs response, in five breast cancer GEO datasets and validated by vitro experiments. In vitro, dihydroartemisinin and artesunate could reverse breast cancer doxorubicin resistance, through inducing autophagy via upregulating LC3B and ATG7.Our study provided a comprehensive landscape of the autophagy-related molecular and tumor microenvironment patterns for cancer progression and resistance, and highlighted the promising potential of drug-induced autophagy in the activation of drug sensitivity and reversal of resistance.